A study of the pathogenesis of Helicobacter pylori negative chronic duodenal ulceration. Issue 6 (June 1993) - McColl, K E; el-Nujumi, A M; Chittajallu, R S; Dahill, S W; Dorrian, C A; el-Omar, E; Penman, I; Fitzsimons, E J; Drain, J; Graham, H
Abstract : In the past five years 12 patients have been identified presenting with chronic duodenal ulcer (DU) disease and with no evidence of current or recent Helicobacter pylori (H pylori) infection. Four of them were taking regular non-steroidal anti inflammatory agents, one was subsequently found to have Crohn's disease of the duodenum, and one to have the Zollinger-Ellison syndrome. The remaining six patients with idiopathic DU disease were remarkable for their absence of the A1 blood antigen gene. Detailed studies of gastric function were performed in these six patients and compared with H pylori positive patients with DU and with healthy volunteers. The median integrated gastrin response in the patients with idiopathic DU (2810 (range 750-8750) ng/l min) was similar to that of the H pylori positive patients with DU (3355 (550-8725)) and higher than that of the H pylori negative healthy volunteers (560 (225-1125)). The median peak acid output in the patients with idiopathic DU (37 mmol/h, range 17-52) was similar to that of the H pylori positive patients with DU (40 (15-57)) and higher than that of the non-ulcer controls (22 (16-29)). The median percentage of a liquid meal retained in the stomach at 60 minutes was less in the patients with idiopathic DU (23 (15-33)) than in H pylori negative healthy volunteers (34 (30-53) p < 0.01). The median percentage of a solid meal retained at 60 minutes was less in the patients with idiopathic DU (54 (9-83)) than in either H pylori negative healthy volunteers (87 (49-95) p<0.01) or H pylori positive patients with DU (79 (51-100) p<0.01). In conclusion, three abnormalities of gastric function are prevalent in patients with H pylori negative idiopathic DU disease - hypergastrinaemia, increased acid secretion, and the one feature distinguishing them from H pylori positive patients with DU - rapid gastric emptying of both liquids and solids. Each of these abnormalities will increase the exposure of the duodenal mucosa to acid and thus explain its ulceration. The absence of the blood group A1 antigen gene is consistent with a genetic basis for the disturbed gastric function linked to the ABO blood group antigen genes.